Characteristics of calcium lignin from pulping waste liquor and application for the treatment middle-stage wastewater of paper making. Issue 5 (23rd February 2023) - Li, Yijing; Zhu, Tian; Yang, Hao; Nong, Guangzai
ABSTRACT: In order to obtain a lignin-based adsorbent with low cost, simple operation and no further modification, a calcium lignin adsorbent was prepared from chemical mechanical pulping (CMP) waste liquor by directly calcification from lime. The calcium lignin was characterized by BET, SEM, TEM, FT-IR and solid-state NMR analyses. The results showed that the molecular structure of the calcium lignin particles did not change when compared to sodium lignin, the formation mechanism of calcium lignin was revealed. The initial COD and lignin contents of CMP waste liquid were 54858 mg/L and 24.39 g/L, the conversion rate of lignin can reach 71.36% when was deal with lime. Thus, most of the lignin resources in the waste liquid were recovered. The middle-stage wastewater (MSWW) of pulping and papermaking was dealt with calcium lignin, the COD removal rate was up to 85.83%. The adsorption isotherms and kinetics were well fitted by the Langmuir model and pseudo-second-order kinetic model, respectively. Lime was regenerated from the used calcium lignin with high-temperature calcination, the conversion rate of calcium ions can reach 83.56%. Overall, the calcium lignin prepared by the one-step method exhibited great potential for effectively removing COD from middle-stage wastewater. GRAPHICAL ABSTRACT: UF0001